Operator decision-making in angiography-only guided revascularization for lesions not indicated for FFR: a QFR-based functional assessment in chronic coronary syndrome - Kanoun Schnur, Sadeek S.; Pranevičius, Robertas; Stark, Cosima; Prunea, Dan; Andreka, Judit; Schmidt, Albrecht; Harb, Stefan; Ruzsa, Zoltan; Zweiker, Robert; Kane, Jesse; Toth, Gabor G. (Frontiers in Cardiovascular Medicine, 2024)
Background Discordance between coronary angiographic findings and invasive functional significance is well-established. Yet, the prevalence of this mismatch in an era increasingly utilizing invasive functional assessments, such as fractional flow reserve (FFR), remains unclear. This study examines the extent of such discrepancies in current clinical practice. Methods This single-center prospective registry included consecutive patients with chronic coronary syndrome (CCS) who underwent elective coronary angiography, with or without revascularization. Coronary angiograms deemed not requiring FFR due to clear anatomical distinctions, either anatomically severe indicating a need for revascularization or mild suggesting no need for intervention, were selected for evaluation. These were then subjected to post-hoc analysis by three independent operators who were blinded to the definitive treatment strategies. Importantly, the post-hoc analysis was conducted in two distinct phases: firstly, a re-evaluation of coronary stenosis, and secondly, a separate functional assessment, each carried out independently. Coronary stenosis severity was assessed visually, while functional relevance was determined by quantitative flow ratio (QFR), calculated using a computational fluid dynamics algorithm applied to angiographic images. Analysis focused on discrepancies between QFR-based functional indications and revascularization strategies actually performed. Results In 191 patients, 488 vessels were analyzed. Average diameter stenosis (DS) was 37 ± 34%, and QFR was 0.87 ± 0.15, demonstrating a moderate correlation (r = −0.84; 95% CI: −0.86 to −0.81, p < 0.01). Agreement with QFR at conventional anatomical cutoffs was 88% for 50% DS and 91% for 70% DS. Mismatches between revascularization decisions and QFR indications occurred in 10% of cases. Discrepancies were more frequent in the left anterior descending artery (14%) compared to the left circumflex (6%) and the right coronary artery (9%; p = 0.07). Conclusion In a cardiac-center where FFR utilization is high, discordance between coronary angiography and functional significance persists, even when operators are confident in their decisions not to use functional interrogation. This gap, most evident in the left anterior descending artery, highlights the potential need for integrated angiography-based functional assessments to refine revascularization decisions in CCS.